Politik Vs Teknis: Problematika Implementasi Simbol ke-Aceh-an - Aklima; Zakki Fuad Khalil; Rahmat Hidayat (Journal of Social and Policy Issues, 2023)
This research focuses on the problems of implementing Acehnese symbols. Where Aceh has special authority in accordance with Law No. 11 of 2006 concerning the Government of Aceh which was born from the Helsinki MoU peace agreement of August 15, 2005. With this agreement, the birth of Qanun No. 3 of 2013 concerning the Flag and Emblem of Aceh which could not be implemented. Because it is contrary to Government Regulation No. 77 of 2007. Where the symbol of the Aceh Government, namely the Star Moon, is considered to contain elements of struggle and separatism. This study focuses on the dynamics of the implementation process of the Aceh flag and emblem symbols as well as the obstacles that occur in the implementation process. The method used is descriptive qualitative with documentation and interview data collection techniques. The results of the study include; There are three indicators that affect political dynamics in the process of implementing the Acehnese symbol, namely (1), Disagreements between the central and regional governments, (2) Overlapping rule of law, (3) Tug-of-war of interests. Meanwhile, obstacles in the implementation process are the content of the policies carried out not in accordance with legal products, the dominance of the interests of the political elite and neglect between the two parties. The conclusion of the problem of implementing symbols to Aceh is that there are complex challenges in the implementation of symbols to Aceh in the form of flags, and emblems. It is necessary to take a sensitive approach and consider local values to achieve good acceptance and integration.